2005
DOI: 10.3758/bf03193640
|View full text |Cite
|
Sign up to set email alerts
|

Target uncertainty does not lead to more distraction by singletons: Intertrial priming does

Abstract: In our everyday lives, we are presented with a wide variety of visual stimuli. For adaptive behavior, it is important to select both objects relevant to our goals and objects that might not be directly relevant but have an intrinsic importance. A key discussion in attention research is the interaction between these goals and the intrinsic qualities of objects in the visual field. The discussion revolves around the concept of attentional capture, defined as the involuntarily drawing of attention.According to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 22 publications
12
85
3
Order By: Relevance
“…But, like the filtering hypothesis, it is not clear why disengagement would become faster with experience, unless one proposes that experience with the distractor itself affects attentional control and capture, which is precisely our view. Finally, there have been many demonstrations of priming in attentional capture (Lamy, Carmel, Egeth, & Leber, 2006;Olivers & Humphreys, 2003;Pinto, Olivers, & Theeuwes, 2005). We view our results as being largely consistent with this literature.…”
Section: Discussionsupporting
confidence: 82%
“…But, like the filtering hypothesis, it is not clear why disengagement would become faster with experience, unless one proposes that experience with the distractor itself affects attentional control and capture, which is precisely our view. Finally, there have been many demonstrations of priming in attentional capture (Lamy, Carmel, Egeth, & Leber, 2006;Olivers & Humphreys, 2003;Pinto, Olivers, & Theeuwes, 2005). We view our results as being largely consistent with this literature.…”
Section: Discussionsupporting
confidence: 82%
“…The absence of an interaction between distractor interference and target feature repetition appears to be directly at odds with recent findings by Pinto, Olivers, and Theeuwes (2005). Their study was similar to the present Experiment 1 but included only the fixed and mixed singleton conditions.…”
Section: Reassessment Of the Notion Of A Default Singleton Detection contrasting
confidence: 56%
“…On the basis of the claim that performance in the fixed and the mixed singleton conditions became similar with respect to distractor interference after one repetition of the target feature, Pinto et al (2005) concluded that the same salience-based mechanism underlies the two conditions and that no feature-based guidance operates in search for a known singleton. However, in their study, RTs in the mixed singleton condition on repeated target feature trials remained substantially higher than those in the fixed singleton condition.…”
Section: Reassessment Of the Notion Of A Default Singleton Detection mentioning
confidence: 99%
“…It should be noted that the increased sensitivity due to priming that we observed in our experiments (and in, e.g., Maljkovic and Nakayama, 1994;Kristjansson et al, 2002;Pinto et al, 2005) is unlike the more the traditional response priming (e.g., Bertelson, 1965;Pashler & Baylis, 1991), in which the facilitation of performance is due to priming of the probable response. In those experiments, performance improves because priming allows the advanced preparation of the most likely response.…”
Section: Discussioncontrasting
confidence: 42%